2010
DOI: 10.1038/scibx.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Curiously strong lipidoids

Abstract: Researchers at Alnylam Pharmaceuticals Inc. and the Massachusetts Institute of Technology have developed a class of lipid-like carriers that are nearly 100 times more efficient at delivering small interfering RNA than previously studied lipid-based carriers.1 The parties are now scaling up production of one of the carriers-dubbed lipidoids-and are optimizing it in rodent and nonhuman primate disease models.If successful, lipidoids could address one of the most significant challenges facing RNAi therapeutics: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Liposomes protect RNAi from being “detected” by RNAses, and if coupled to specific antibodies or ligands can deliver the particles specifically into melanoma cells. In a recent report researchers at Alnylam Pharmaceuticals Inc. and the Massachusetts Institute of Technology listed ~ 1200 different class of lipid-like barriers called “lipidoids” that are about 100 times more efficient at delivering small interfering RNA than the earlier reported lipid-based barriers [151]. With this technology one can use a loading ranging from 3 to 30μg/kg of siRNA compared to commonly used regular lipid barriers that require at least 1 mg/kg to get more than 50% gene silencing [151].…”
Section: 0 Use Of Nanotechnology To Target Mapk Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes protect RNAi from being “detected” by RNAses, and if coupled to specific antibodies or ligands can deliver the particles specifically into melanoma cells. In a recent report researchers at Alnylam Pharmaceuticals Inc. and the Massachusetts Institute of Technology listed ~ 1200 different class of lipid-like barriers called “lipidoids” that are about 100 times more efficient at delivering small interfering RNA than the earlier reported lipid-based barriers [151]. With this technology one can use a loading ranging from 3 to 30μg/kg of siRNA compared to commonly used regular lipid barriers that require at least 1 mg/kg to get more than 50% gene silencing [151].…”
Section: 0 Use Of Nanotechnology To Target Mapk Signalingmentioning
confidence: 99%
“…In a recent report researchers at Alnylam Pharmaceuticals Inc. and the Massachusetts Institute of Technology listed ~ 1200 different class of lipid-like barriers called “lipidoids” that are about 100 times more efficient at delivering small interfering RNA than the earlier reported lipid-based barriers [151]. With this technology one can use a loading ranging from 3 to 30μg/kg of siRNA compared to commonly used regular lipid barriers that require at least 1 mg/kg to get more than 50% gene silencing [151]. Clinical efficacy of this approach for targeting the MAP kinase pathways remains to be demonstrated [152].…”
Section: 0 Use Of Nanotechnology To Target Mapk Signalingmentioning
confidence: 99%
“…Lipidoids—another class of lipid‐based nanoparticles—have a similar structure to liposomes and are synthesized by conjugating alkyl‐acrylamides and amine molecules. They require fewer steps for fabrication compared to liposomes, which makes them preferential for high‐throughout analysis of different therapeutic agents . Moreover, it has been shown that at a low serum level (2%), the transfection of human umbilical vein endothelial cells (HUVECs) using lipidoid was comparable to Lipofectamine 2000.…”
Section: Sirna Dds For Bone Regenerationmentioning
confidence: 99%
“…They require fewer steps for fabrication compared to liposomes, which makes them preferential for high-throughout analysis of different therapeutic agents. (96) Moreover, it has been shown that at a low serum level (2%), the transfection of human umbilical vein endothelial cells (HUVECs) using lipidoid was comparable to Lipofectamine 2000. However, at a normal serum level (10%), lipidoids had superior transfection efficiency compared to Lipofectamine 2000.…”
Section: Lipid-based Ddsmentioning
confidence: 99%
“…Moreover, lipidoids, which possess a similar chemical structure to liposomes, are another new type of lipid-based nanoparticle. Lipidoids gained significantly higher transfection efficiency over Lipofectamine 2000 in human umbilical vein endothelial cells (HUVECs) at a low serum level (2%) (Fulmer, 2010). Ramasubramanian et al performed delivery of BMP-2 DNA along with Noggin and guanine nucleotide binding protein alpha-stimulating activity polypeptide (GNAS) targeting siRNA in an immortalized human foetal osteoblast cell line (hFOB1.19) using a lipidoid called NA114, which was previously reported to be an efficient siRNA carrier (Cho et al, 2009).…”
Section: Sirna-mediated Bone Formation and Resorptionmentioning
confidence: 99%